Hepatocellular Carcinoma Future Outlook - Kaseb, Ahmed O. (IntechOpen, 2013)
Hepatocellular carcinoma (HCC) develops as a consequence of underlying chronic liver disease, most commonly cirrhosis. Therefore, HCC management draws on the expertise of a range of medical specialists. Many components of current novel therapeutic modalities for HCC are discussed in the current version of the book within the framework of a multidisciplinary approach with special emphasis on emerging treatment approaches and research strategies. This book is the essential clinical guide for oncologists, hepatologists, surgeons, and all physicians and researchers involved in the care of patients with HCC. I would like to thank the authors for their significant efforts in bringing this edition to life. This book is a tribute to their continued dedication to improving HCC outcome.